1997
DOI: 10.1021/jp9712967
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Structure and Energetics for the Molecular and Dissociative Adsorption of NH3 on Si(100)-2 × 1

Abstract: We predict the structures and detailed energetics for the dissociative adsorption of NH3 to form NH2 and H adsorbed on a single Si dimer on the Si(100)-2 × 1 surface at the MRSDCI (multireference single and double excitation configuration interaction) level of theory. We predict that this dissociation involves two steps:  (i) barrierless molecular chemisorption of NH3 followed by (ii) activated N−H bond cleavage of NH3(a) to form NH2(a) + H(a). While the second step involves a barrier, its relatively small hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
66
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 28 publications
17
66
4
Order By: Relevance
“…14,15 Since silicon atoms on the surface remain unsaturated even after the ͑2 ϫ 1͒ reconstruction, this surface is very reactive. For example, ammonia ͑NH 3 ͒ and water ͑H 2 O͒ adsorb dissociatively, even at cryogenic temperatures, to form ͑Si͒NH 2 and ͑Si͒H moieties in the former case [16][17][18][19][20][21][22][23][24][25][26] and ͑Si͒OH and ͑Si͒H species in the latter. [27][28][29][30] Dissociated species may occupy the same dimer or neighboring dimers, known respectively as intradimer and interdimer dissociations.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Since silicon atoms on the surface remain unsaturated even after the ͑2 ϫ 1͒ reconstruction, this surface is very reactive. For example, ammonia ͑NH 3 ͒ and water ͑H 2 O͒ adsorb dissociatively, even at cryogenic temperatures, to form ͑Si͒NH 2 and ͑Si͒H moieties in the former case [16][17][18][19][20][21][22][23][24][25][26] and ͑Si͒OH and ͑Si͒H species in the latter. [27][28][29][30] Dissociated species may occupy the same dimer or neighboring dimers, known respectively as intradimer and interdimer dissociations.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies observed that ammonia adsorbs dissociatively on Si͑100͒ even at cryogenic temperatures, [1][2][3][4][5][6] and after some controversy regarding the nature of the dissociation products, it was established that NH 3 dissociates on this surface to form ͑Si͒NH 2 and Si-H, which was confirmed by theoretical studies. [31][32][33][34] Dissociation was found to be possible even at low temperatures because of the high reactivity of the Si͑100͒ surface. 35 This surface can be best described as formed by rows of surface dimers, which result from the ͑2 ϫ 1͒ reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…44 Thus, the adsorption of NH 3 on this surface can be viewed as a nucleophilic attack of the N lone pair onto a down Si atom, a process that was found to be barrierless. [31][32][33][34]36 This initial process forms a tetracoordinated nitrogen atom ͑N 4C ͒ and further stabilization of this structure is achieved by dissociation, through the cleavage of a N-H bond and the formation of the stable species ͑Si͒NH 2 and Si-H. 37,38 Since the nucleophilic up atom of the silicon dimer containing the adsorbed molecule can facilitate the cleavage of the N-H bond, the intradimer dissociation was widely assumed, [31][32][33][34]36 although recent investigations, both theoretical [41][42][43] and experimental, 29,30 suggest that interdimer dissociation might be a significant pathway as well. Nevertheless, since the intradimer dissociation was widely accepted, other researchers studied the long-range configuration of adsorbed species, finding two possible configurations: ͑1͒ where NH 2 groups are located on the same side of the silicon dimer row ͑which we will refer to as aligned͒ and ͑2͒ where NH 2 groups alternate with H species along the same side of a silicon dimer row ͑which we will refer to as alternate͒.…”
Section: Introductionmentioning
confidence: 99%
“…By providing information on the possible mechanisms involved in the growth of new films, it has the potential to aid in the development and improvement of processes for the production of films of technological interest. Motivated by the high reactivity of ammonia in experiments of chemical vapor deposition (CVD) at high temperatures, studies on the growth of silicon nitride (Si 3 N 4 ) films, focusing mainly on the interaction of NH 3 molecules with the silicon surface have been reported in the literature [1][2][3]. Another possibility of growth involves a deposition process where an atomic ion beam with a known kinetic energy collides with the surface.…”
Section: Introductionmentioning
confidence: 99%